1995
DOI: 10.1038/ki.1995.213
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for nitric oxide in modulating the functional cyclosporine toxicity by arginine

Abstract: The renal damage consequent to cyclosporine A (CsA) administration ranges from hemodynamic alterations to irreversible chronic lesions. The initial vasoconstriction depends upon the imbalance between the various modulators of the renal vascular tone, among which the most powerful are endothelins and nitric oxide (NO). CsA could play a crucial role by inhibiting the Ca++/calmodulin-mediated activation of the constitutive NO synthase (NOS) isoform, which converts L-arginine (L-Arg) into NO and citrulline, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 33 publications
3
26
1
Order By: Relevance
“…Another approach has been to use l-arginine or molsidomine for the prevention of CNI nephrotoxicity. In rats, l-arginine greatly ameliorated kidney dysfunction induced by cyclosporine (373,374), but not in all studies (375). In humans, no effect of l-arginine was observed (376).…”
Section: Other Approachesmentioning
confidence: 99%
“…Another approach has been to use l-arginine or molsidomine for the prevention of CNI nephrotoxicity. In rats, l-arginine greatly ameliorated kidney dysfunction induced by cyclosporine (373,374), but not in all studies (375). In humans, no effect of l-arginine was observed (376).…”
Section: Other Approachesmentioning
confidence: 99%
“…[24][25][26] Bloom et al 25 and Gallego et al 18 found that L-arginine reversed CsA-induced vasoconstriction in anaesthetised and conscious rats. Gallego also showed that simultaneous administration of L-arginine with CsA significantly prevented the toxic effects of CsA.…”
Section: Discussionmentioning
confidence: 99%
“…The vasoconstriction is thought to result from impaired endothelial cell function, leading to reduced production of vasodilators. 7,8 The results of sustained renal vasoconstriction include vascular angiopathy, altered mesangial cell contraction, tubular atrophy, and eventually interstitial fibrosis, leading to permanent reduction in renal function. 6,32 The principal finding of the current study was an association between the Glu298Asp SNP of the NOS3 gene and an increased risk of CKD after LT.…”
Section: Discussionmentioning
confidence: 99%
“…8,[38][39][40][41][42][43][44][45][46][47][48][49] In animals, increased NO production by agents such as L-arginine or molsidomine has been shown to ameliorate the CNI nephrotoxicity, whereas depletion of NO by L-NAME, a competitive inhibitor of eNOS, augments the nephrotoxicity. 48 These data indicating the importance of NO in the pathogenesis of CNI nephrotoxicity suggest that the NOS3 SNP found in this study may have a mechanistic role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation